Toxicidade de compostos ativos contra larvas de Aedes aegypti em modelo de Artemia sp. - Nunes, Rafaela Karolina Viana (2019)
Dengue, yellow fever, chikungunya and Zika are diseases transmitted by the Aedes aegypti Linn mosquito. (Diptera: Culicidae). The control of this vector, through nonselective chemical pesticides, can bring negative impacts to non-target organisms, essential for the maintenance of ecosystems, besides generating strains resistant to its effects. New alternatives need to be more selective and ecologically viable. In this sense, the Laboratory of Pharmaceutical Chemistry (LQF) located at the Federal University of Sergipe has been developing new active molecules against Larvae of Ae. aegypti. to reduce the incidence of these diseases. To advance studies on vector control with potentially larvicide molecules that cause minimal toxic effects to nontarget organisms, the present study aimed to evaluate the acute toxicity of larvicide compounds from the LQF Library, in front of the artemia bioindicator, through the analysis of the selectivity of these substances. Artemia is one of the widely used organisms in environmental analysis because it presents a clear response to small variations in the quality of the environment. For the calculation of selectivity, the larvicidal activity of the compounds previously synthesized in the LQF was compared with the lethal activity 50% (LC50) for Artemia sp nauplios. The CL50 against artemia was obtained in trials with varied concentrations of larvicide compounds in artificial marine water. The analyses showed a variable selectivity index (Is) among all compounds tested, and the indole derivatives were those that presented highly promising selectivity, especially the derivative 1-[(4-methylphenyl)sufonil]-1H-indol that presented IS >6148. Other ecotoxicological studies should be carried out to evaluate the effects of these compounds against different aquatic biota organisms and trophic levels.